2D Seismic Reflection Study of the Cretaceous-Tertiary Period in Qasab-Jawan Area in Northwestern Iraq - Shehab, Marwa H.; Ali, Kamal K. (Iraqi Journal of Science, 2021)
A seismic study was conducted to re-interpret the Qasab and Jawan oil field in northern Iraq, south of the city of Mosul, by reprocessing and interpreting many seismic sections of a number of field surveys that included the field area. Two reflectors are detected, represented by Hartha Formations which were deposited during the Cretaceous age and Euphrates Formation which was deposited during the Tertiary age in order to stabilize the structural image of this field. The study was achieved by reinterpreting seismic sections using the Petrel program, where time, velocity and depth maps were prepared for the two formations.The study showed that the Qasab and Jawan fields generally consist of a structural closure located at the wells of the northern dome. This closure extends to the south east and deviates towards the east in the form of a structural rift. The study concluded the existence of a transverse fault that cuts Qasab and Jawan structures, forming a structural trap that represents the southern part of Qasab structure.